Cognitive Demand in Standardized Mathematics Assessments in Spain and Portugal (Revista Lusófona de Educação, 2026)
Standardized assessments constitute a valuable tool for informing educational policy. The aim of this study is to quantify the cognitive demands of the Mathematics tests administered in 2024 and 2025 in the autonomous community of Galicia (Spain) and in Portugal, and to compare them with the curricular demands of the corresponding grade levels, with Lange’s distribution, and with the PISA and TIMSS assessments. To this end, the cognitive processes of the revised Bloom’s taxonomy are used. The methodology is mixed, with a descriptive approach. In Galicia, diagnostic assessments for students aged 9 and 13, as well as the university entrance examinations (age 17), are analysed; in Portugal, the final examinations taken at ages 14, 16, and 17 are examined. Information from each test is recorded in a data collection sheet structured as a double-entry table (items / cognitive processes). The resulting data are analysed statistically. The findings show that the cognitive demands of these tests are higher than those associated with Lange’s model, but lower than the curricular demands and those observed in PISA and TIMSS. The distributions of cognitive processes show significant differences with respect to PISA and TIMSS. Extending this study to other countries would make it possible to design demand maps and to develop cognitive distributions better aligned with different national contexts.